Comparison among three types of relay start in competitive swimming - Takeda, T.; Takagi, H.; Tsubakimoto, S. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of the present study was to evaluate the effectiveness of no-step, single-step and double-step relay starts for swimmers. Eight male collegiate swimmers participated in the present study. For each type of start, each swimmer performed six trials of relay starts with maximum effort. Ground reaction forces were measured using a Kistler force plate to calculate the take-off velocity and take-off angle from the force data. Relay times were measured by counting the number of video frames obtained by a high-speed camera. No significant difference in the horizontal take-off velocity was observed. The relay times decreased significantly in the order nostep, single-step and double-step starts (P < 0.05). Eight trials among all the trials for the step starts resulted in incorrect foot placement on the edge of the block. No-step starts resulted in better performance than step starts.